Organic Electroluminescent Materials Possessing Intra- and Intermolecular Hydrogen Bond Interactions: A Mini-Review - Liu, Xinyong; Li, Jingwei; Qiu, Xu; Pan, Yuyu (Frontiers in Chemistry, 2022)
Organic light-emitting diodes (OLEDs) have been the predominance technology in display applications, owing to their superiorities of light weight, flexibility, power conservation and environmental friendliness and so on. Organic emitters are essential for the full color OLEDs displays. The intrinsic properties of organic emitters determine the devices performance. Especially, the aggregation structure of emitters is crucial for color purity and efficiency. Intra- and intermolecular interactions, such as hydrogen-bond (H-bond), could inhibit the structural vibrations and torsions, which have vital effect on the stability of emitting layer (EML) films and optoelectronic properties of emitting materials. Hence, by regulating the H-bond interaction, the desired properties could be obtained. This mini-review mainly focuses on the high-performance blue, green, and red organic emitters from the perspective of influence of intra-/intermolecular H-bond interactions on the optoelectronic properties.